2006
DOI: 10.1097/01.mlg.0000192173.00498.ba
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Posterior Laryngitis With Esomeprazole

Abstract: This study provides no evidence of a therapeutic benefit of treatment with esomeprazole 40 mg twice daily for 16 weeks compared with placebo for signs and symptoms associated with CPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
255
2
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(271 citation statements)
references
References 25 publications
7
255
2
7
Order By: Relevance
“…In a large randomized, placebo-controlled, multicenter trial of 145 patients, Vaezi et al 75 were unable to demonstrate that 40 mg esomeprazole twice daily for 16 weeks was better than placebo for symptom resolution or improvement in laryngeal signs of laryngopharyngeal reflux. A subsequent meta-analysis of the placebo-controlled studies in laryngopharyngeal reflux has reported minimal therapeutic benefit of PPIs over placebo.…”
Section: -74mentioning
confidence: 99%
“…In a large randomized, placebo-controlled, multicenter trial of 145 patients, Vaezi et al 75 were unable to demonstrate that 40 mg esomeprazole twice daily for 16 weeks was better than placebo for symptom resolution or improvement in laryngeal signs of laryngopharyngeal reflux. A subsequent meta-analysis of the placebo-controlled studies in laryngopharyngeal reflux has reported minimal therapeutic benefit of PPIs over placebo.…”
Section: -74mentioning
confidence: 99%
“…The RFS is an 8-item clinical severity scale based on findings during fiberoptic laryngoscopy. However, this RFS system has been criticized to have high inter-or intra-observer variability and low specificity for reflux laryngitis [6,10,19] . Therefore, it is very important to exclude meticulously other potential etiologies that can lead to laryngeal irritation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were excluded from the study if they had a history of respiratory or gastrointestinal malignancy; radiation therapy to the head and neck, lung, or gastrointestinal tract; gastroesophageal surgery; use of H 2 -receptor antagonists or proton pump inhibitors in previous 1 mo; past or present smoker; excessive alcohol consumption; chronic cough attributable to known chronic pulmonary or tracheobronchial disease; professional voice users (e.g. singer, teacher); excessive voice use; exposure to occupational or environmental pollutants; history of seasonal allergic rhinitis; pharyngolaryngeal infection in the previous 3 mo; tracheal intubation in the previous 12 mo and use of inhaled corticosteroids [10,11] .…”
Section: Recruitment Of Patientsmentioning
confidence: 99%
“…Attempts were made to contact study authors for additional information needed for full analysis of their data. [12][13][14][15][16] Results…”
Section: Analysis Of Therapeutic Gainmentioning
confidence: 99%